INK128 Exhibits Synergy with Azoles against Exophiala spp. and Fusarium spp. - Gao, Lujuan; Sun, Yi; He, Chengyan; Li, Ming; Zeng, Tongxiang; Lu, Qiaoyun (Frontiers in Microbiology, 2016)
Infections of Exophiala spp. and Fusarium spp. are often chronic and recalcitrant. Systemic disseminations, which mostly occur in immunocompromised patients, are often refractory to available antifungal therapies. The conserved target of rapamycin (TOR) orchestrates cell growth and proliferation in response to nutrients and growth factors, which are important for pathogenicity and virulence. INK128 is a second-generation ATP-competitive TOR inhibitor, which binds the TOR catalytic domain and selectively inhibits TOR. In the present study, we investigated the in vitro activities of INK128 alone and the interactions of INK128 with conventional antifungal drugs including itraconazole, voriconazole, posaconazole, and amphotericin B against 18 strains of Exophiala spp. and 10 strains of Fusarium spp. via broth microdilution checkerboard technique system adapted from clinical and Laboratory Standards Institute broth microdilution method M38-A2. INK128 alone was inactive against all isolates tested. However, favorable synergistic effects between INK128 and voriconazole were observed in 61% Exophiala strains and 60% Fusarium strains, despite Fusarium strains exhibited high MIC values (4-8 μg/ml) against voriconazole. In addition, synergistic effects of INK128/itraconazole were shown in 33% Exophiala strains and 30% Fusarium strains, while synergy of INK128/posaconazole were observed in 28% Exophiala strains and 30% Fusarium strains. The effective working ranges of INK128 were 0.125-2 μg/ml and 1-4μg/ml against Exophiala isolates and Fusarium isolates, respectively. No synergistic effect was observed when INK128 was combined with amphotericin B. No antagonism was observed in all combinations. In conclusion, INK128 could enhance the in vitro antifungal activity of voriconazole, itraconazole and posaconazole against Exophiala spp. and Fusarium spp., suggesting that azoles, especially voriconazole, combined with TOR kinase inhibitor might provide a potential strategy to the treatment of Exophiala and Fusarium infections. However, further investigations are warranted to elucidate the underlying mechanism and to determine possible reliable and safe application in clinical practice.